The role of childhood traumas on father-child sexual communication language: Self-esteem, social anxiety and sexual education - Ibrahim Güngör; Ismihan Zeliha Artan (PLoS ONE, 2026)
The aim of the study was to examine the direct and indirect associations between fathers’ childhood abuse experiences and their levels of self-esteem, social anxiety, attitudes towards sexual education and sexual communication language levels with their children. The sample of the study consisted of 587 fathers. Data were collected through ‘Childhood Trauma Questionnaire Short Form’, ‘Social Anxiety Scale Short Form’, ‘Rosenberg Self-Esteem Scale’, ‘Attitude Towards Sexual Education Scale’, ‘Sexual Communication Scale for Parents’ and ‘Demographic Information Form’. The data were analyzed using Pearson correlation coefficients and path analysis conducted in SPSS 24 and R. The findings showed that childhood abuse experiences were positively correlated with social anxiety and negatively correlated with self-esteem and father’s sexual communication language with his child. As a result of the path analysis, it was found that childhood abuse experiences were positively associated with social anxiety and negatively associated with self-esteem and sexual communication language. Self-esteem was negatively associated with social anxiety and positively associated with sexual communication language; social anxiety was negatively associated with attitudes towards sexual education and sexual communication language; and attitudes towards sexual education were positively associated with sexual communication language. Childhood abuse experiences were also indirectly associated with social anxiety, attitudes towards sexual education, and sexual communication language through self-esteem and social anxiety. Overall, the findings were discussed within the framework of father-child sexual communication language and fathers’ involvement in the sexual education process.